Pelatihan Pembelajaran Daring Menggunakan Google Class Room dan Google Meet di SMP Pelita Medan - Raju Gobal; Suhendra (Jurnal Pengabdian Masyarakat, 2022)
During the Covid-19 pandemic, many learning activities that were initially carried out face-to-face had to be carried out online. Many schools conduct learning using WhatsApp. This is because many teacher human resources in Medan in particular do not have knowledge of existing learning media technologies such as Google Class Room and Meet. Online Learning Training Programs Using Google Class Room and Google Meet at Pelita Medan Middle School are conducted to train Pelita Medan Middle School teachers to have knowledge and competence in using Google Class Room and Google Meet in the process of teaching and learning activities. After using Google Class Room and Google Meet learning media, it is hoped that the teaching and learning process will get maximum results in the delivery of learning material.